2018
DOI: 10.15560/14.6.1058
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and molecular identification of Geophagus sveni Lucinda, Lucena & Assis, 2010 (Cichlidae, Cichliformes) from the Paraná river basin, Argentina

Abstract: During 2015, we collected several specimens of a cichlid tentatively assigned to Geophagus in Yacyretá reservoir in the Paraná river basin (Argentina). By means of morphological and molecular evidence, we identified these specimens as Gephagus sveni, a species known from middle portion of the Tocantins River. Here we report the presence of the genus Geophagus (sensu stricto) in Argentina for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…2 ). Benitez et al (2018) found minimal or no genetic divergence between these individuals and suggested that all specimens were G. sveni misidentified as G . “ proximus ”.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Benitez et al (2018) found minimal or no genetic divergence between these individuals and suggested that all specimens were G. sveni misidentified as G . “ proximus ”.…”
Section: Discussionmentioning
confidence: 99%